2008
DOI: 10.1080/17518250802482505
|View full text |Cite
|
Sign up to set email alerts
|

Diels-Alder reactions in the presence of a minimal amount of water

Abstract: Diels-Alder reactions of neat reactive dienes and dienophiles are frequently vigorous and have a limited preparative value. It is possible to control the temperature of multi-gram scale Diels-Alder reactions by adding a minimal amount of water to neat reactants. In addition, the presence of water resulted in an increased reaction rate and formation of a higher purity product. The use of minimal amounts of other solvents, with lower heat capacities, did not give good results. Furthermore, some dienophiles, e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…It has been witnessed that the reaction rate was greater in organic solvents (CH 2 Cl 2 and THF) along with catalytic amount of water than in the case of pure organic solvents. This was also the case only with catalytic amount of water in a solvent‐free system and it was in accordance with the studies explained by Dragojlovic and co‐workers . The above study showed that the enhancement of rate in the presence of catalytic amounts of water probably due to water catalysis via hydrogen bonding effect.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It has been witnessed that the reaction rate was greater in organic solvents (CH 2 Cl 2 and THF) along with catalytic amount of water than in the case of pure organic solvents. This was also the case only with catalytic amount of water in a solvent‐free system and it was in accordance with the studies explained by Dragojlovic and co‐workers . The above study showed that the enhancement of rate in the presence of catalytic amounts of water probably due to water catalysis via hydrogen bonding effect.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, the purity of products was higher in reactions performed in water (which were confirmed by its pure NMR and GC‐MS spectra). This is possible because water in the reaction mixture, may be, lowering the temperature of exothermic reaction …”
Section: Resultsmentioning
confidence: 99%
“…Windmon et al. reported a rate increase after the addition of water in this reaction . However, it is impossible to determine whether the reported “on water” effect applies to this system as Sc(OTf) 3 is water sensitive.…”
Section: Resultsmentioning
confidence: 88%
“…The starting material was prepared in another green chemistry experiment Á reaction of 2,3-dimethyl-1,3-butadiene and acetylenedicarboxylic acid in water (14). In the laboratory session following this experiment, we discussed both the reaction mechanism and the green chemistry aspects of this exercise.…”
Section: Green Chemistry Aspects Of the Laboratory Exercisementioning
confidence: 99%